CATTLE HEALTH MONITORING BASED ON IOT - T. , Sreelekha; P. , Dass (International Journal of Psychosocial Rehabilitation, 2020)
Animal breeding is an increasingly popular enterprise in which animals are fed food and other products. The livestock farm’s output is largely determined by the animal’s health conditions. The profitability of the entire farm will dramatically decline from cattle with a communicable disease. Therefore, unhealthy cattle should be identified. IoT may play a significant role in the creation of an autonomous health surveillance network for animals in this sense. A framework comprising data storage, mobile nodes, and an IoT cloud platform is built in this project. The data collection node is fed by different sensors for the identification of animal health parameters and is transferred to the mobile node. The smart phone node acts as a portal into the IoT cloud network for data processing of sensing data to recognize sick animals and notifies the farm owner and veterinarian.